A distributed secret share update scheme with public verifiability for ad hoc network - Zhenhua, Chen; Shundong, Li; Qianhong, Wu; Qiong, Huang (Security and communication networks, 2015)
In this paper, a distributed secret share update scheme with public verifiability for ad hoc network is proposed, in which the system secret key is collaboratively generated by k nodes or more, instead of by a centralized key generation center. To prevent a passive adversary from collecting other nodes' shares to compromise the system key over a long period, each node can periodically refresh its share without changing the system key. At the same time, to resist an active adversary to forge partial share and even to solve the accusation problem, any one can publicly verify the correctness of partial shares submitted by other nodes in the share update phase. To achieve our goals, we explore the technique of verifiable encryption with additive homomorphism and that of threshold cryptography. The analysis shows that the proposed scheme is more secure and efficient than the previous schemes for ad hoc networks. Copyright © 2014 John Wiley & Sons, Ltd. (1) We design a distributed secret share update scheme with public verifiability for MANET. Our goals are as follows: First, it must not have a single point of failure because mobile nodes deployed in hostile environments are subject to attacks. Second, it should be compromise‐tolerant, meaning that the compromise of a certain number of nodes does not harm the communication security between uncompromised nodes. Third, it should be able to efficiently and securely update and publicly verify the shares of system key. Last, there should be efficient schemes to recover a correct system key. (2) In this paper, we explore the technique of verifiable encryption with additive homomorphism and that of threshold cryptography. A distributed secret share update scheme with public verifiability for ad hoc network is proposed.